KEMAMPUAN BERPIKIR KRITIS SISWA MTS DALAM MENYELESAIKAN MASALAH BANGUN DATAR SEGIEMPAT - Erlita Erlita; Dori Lukman Hakim (IKIP Siliwangi, 2022)
The importance of critical thinking skills is possessed by every student in order to be able to solve math problems appropriately. This article aims to provide an overview of the ability of MTs students in critical thinking in solving quadrilateral material problems. The picture to be studied related to students' ability to interpretation, analysis, evaluation, inference, and explanation. The subject in this article is class IX students in one of the MTs in Karawang Regency with a total of 16 students who will be categorized based on high, medium, and low. Data collection technique using tests in the form of 5 questions of description in quadrilateral material and interviews. The method used is qualitative descriptive. The data analysis techniques in this article based on Miles &Huberman, namely collecting data, data reduction, data presentation, and verification. The results showed that students' critical thinking skills were in 3 categories, namely 6% in high categories, 75% in moderate categories, and 19% in low categories. This shows that the ability to think students in completing quadrilateral problems is relatively moderate, meaning that students' ability to complete quadrilateral based on critical thinking steps has not been maximized.